HUBUNGAN ANTARA TINGKAT PENDIDIKAN IBU DAN POLA ASUH GIZIDENGAN KEJADIAN KARIES GIGI PADA ANAK BALITA DI DESA MRANGGENSUKOHARJO - PRANYATA DEWI, DIAN, Endang Nur W, S.St., M.Si.Med, Luluk Ria Rakhma, S.Gz., M.Gizi (2015)
DEPARTMENT OF NUTRITION SCIENCE FACULTY OF HEALTH SCIENCE MUHAMMADIYAH UNIVERSITY OF SURAKARTA BACHELOR THESIS ABSTRACT DIAN PRANYATA DEWI. J310110059 THE CORRELATION BETWEEN MOTHER'S EDUCATION LEVEL AND THE NUTRITION PARENTING MODEL AND DENTAL CARIES INCIDENT IN CHILDREN IN MRANGGEN SUKOHARJO. Introduction: Dental caries is a disease that happens in about 90 % children. Dental caries in children will have an impact on the growth and development of teeth. The level of education affects mother's knowledge, it will affect parents' attitude in taking care their children. The better information obtained, the better they educate their children. Objective: This research aimed to determine the correlation between mother's education level, the nutrition parenting model, and dental caries children in Mranggen, Sukoharjo. Research method: This research was an observational study with cross-sectional design. The subject were 81 toddlers aged 24-59 months and the mothers were being respondents. Data on mother's education level and nutrition parenting model were obtained through questionnaires and interviews. Sampling technique proportional random sampling. Analysis of data in this research used the chi -square tests. Results: Most of mothers had primary education level (69.1%). Mothers who had a poor nutrition parenting models was 59.3%. Number of children with dental caries was 64.2%. Mothers with primary education level and had dental caries toddler was 67.9%, which was greater than mothers who had a higher education level. Mothers who had poor nutritions parenting models and children with had dental caries was 68.8%, which was higher compared to those good of parenting. There was no relationship between the level of education with dental caries (p = 0.437). No association beetween parenting and dental caries (p = 0.427). Conclusion: There was no correlation between mother's education level the nutrition parrenting model and dental caries in children in Mranggen Sukoharjo. Keywords: education level, parenting, dental caries Bibliography:46:1993-2014